Localization of IgG Antigenic Sites in Goat Testicular Tissue - R. K. Sharma, A. K. Goyal (Journal of Applied Pharmaceutical Science, 2015)
Testis is the tissue with immune privilege which is maintained by blood-testis barrier to protect autoimmunogenic components of testis. IgG have binding affinity for CD16, CD32 and CD64 receptors present on various immune cells. Present study was conducted to investigate the IgG antigenic sites in the testicular tissue of goat. The paraffin embedded histological sections were processed for immunohistochemistry protocol using Anti Mouse IgG FITC conjugate antibodies and observed under fluorescence microscope. Strong reaction was observed in epithelial lining of seminiferous tubule and moderate reaction was observed in lumen of seminiferous tubules and interstitial space. Present studies indicate that the most of IgG antigenic components i.e. CD16, CD32 and CD64 receptors were located in these sites. Current work will help in understanding of immune privilege and provide a baseline on which further studies can be conducted.
Keywords: Testis, Immunohistochemistry, Immune cells, Fluorescence.